Nephrogenic Adenoma of the Urinary Bladder after Kidney Transplantation: Long-Term Follow-Up - Iftikhar Khan; Mahmoud Obeid; Nasreen Hasan; Fayyad Jaradat; Bodhisatwa Sengupta; Mahmoud Tabbal; Abdullah Alsaif; Mansour Tawfeeq; Mohammad Al Qahtani (Case Reports in Transplantation)
Nephrogenic adenoma is a rare lesion that consists of epithelial cells arranged in tubular form, resembling tubules in the renal medulla, and is found usually in the urinary bladder although it can occur anywhere in the transitional epithelium of the lower urinary tract. The first case of nephrogenic adenoma of the urinary bladder was reported before the first kidney transplantation, and the lesion has been reported in patients with and without renal transplantation. The origin of cells in nephrogenic adenoma is debated and has been postulated to arise from cells of embryonic origin or from metaplasia secondary to chronic irritation or from implantation of allograft cells in patients with kidney transplantation. The long-term outcome and potential to convert into malignancy are not established, and therefore, there are no recommendations on how to follow up these patients. We present a case of a patient who was found to have nephrogenic adenoma of the urinary bladder during his second kidney transplantation from a cadaveric donor. He had undergone living donor kidney transplantation previously which subsequently failed. The patient did not manifest any symptoms of nephrogenic adenoma. During a follow-up period of 5 years, he has not manifested any symptoms related to nephrogenic metaplasia. Histopathological examination 5 years after the second transplantation did not show any malignant change. It can be concluded that nephrogenic adenoma is likely to behave in benign fashion post kidney transplantation.